Clinical and Epidemiological Aspects of Diphtheria: A Systematic Review and Pooled Analysis. (19th August 2019) - Truelove, Shaun A; Keegan, Lindsay T; Moss, William J; Chaisson, Lelia H; Macher, Emilie; Azman, Andrew S; Lessler, Justin
Abstract: Background: Diphtheria, once a major cause of childhood morbidity and mortality, all but disappeared following introduction of diphtheria vaccine. Recent outbreaks highlight the risk diphtheria poses when civil unrest interrupts vaccination and healthcare access. Lack of interest over the last century resulted in knowledge gaps about diphtheria's epidemiology, transmission, and control. Methods: We conducted 9 distinct systematic reviews on PubMed and Scopus (March–May 2018). We pooled and analyzed extracted data to fill in these key knowledge gaps. Results: We identified 6934 articles, reviewed 781 full texts, and included 266. From this, we estimate that the median incubation period is 1.4 days. On average, untreated cases are colonized for 18.5 days (95% credible interval [CrI], 17.7–19.4 days), and 95% clear Corynebacterium diphtheriae within 48 days (95% CrI, 46–51 days). Asymptomatic carriers cause 76% (95% confidence interval, 59%–87%) fewer cases over the course of infection than symptomatic cases. The basic reproductive number is 1.7–4.3. Receipt of 3 doses of diphtheria toxoid vaccine is 87% (95% CrI, 68%–97%) effective against symptomatic disease and reduces transmission by 60% (95% CrI, 51%–68%). Vaccinated individuals can become colonized and transmit; consequently, vaccination alone can only interrupt transmission in 28% of outbreak settings, making isolation and antibiotics essential. While antibiotics reduce the duration of infection, they must be paired with diphtheria antitoxin to limit morbidity. Conclusions: Appropriate tools to confront diphtheria exist; however, accurate understanding of the unique characteristics is crucial and lifesaving treatments must be made widely available. This comprehensive update provides clinical and public health guidance for diphtheria-specific preparedness and response. Abstract : Although largely forgotten, diphtheria remains a significant outbreak threat. Through systematic review and reanalysis, we provide a comprehensive summary of the clinical and epidemiologic aspects of diphtheria, with insights into transmission, treatment, and control.